2021
DOI: 10.1097/cce.0000000000000473
|View full text |Cite
|
Sign up to set email alerts
|

Written Care Summaries Facilitate Communication Between Families and Providers of ICU Patients: A Pilot Study

Abstract: OBJECTIVES: ICU providers may invite families to participate in daily rounds to inform them of the patient’s condition and to support their emotional well-being. Daily written summaries of care may provide complementary benefits. DESIGN: Qualitative interviews with surrogates of ICU patients who received daily written summaries of care. SETTING: Single, urban academic medical center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Primary care physicians wanted better information sharing with patients and families about patient's ICU course and potential post-ICU complications [8,9], particularly when family involvement in the ICU was restricted [10][11][12]. Narrative, written, plain language information about a patient's ICU stay, available after discharge, which can be discussed with outpatient providers, may alleviate some of these problems [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Primary care physicians wanted better information sharing with patients and families about patient's ICU course and potential post-ICU complications [8,9], particularly when family involvement in the ICU was restricted [10][11][12]. Narrative, written, plain language information about a patient's ICU stay, available after discharge, which can be discussed with outpatient providers, may alleviate some of these problems [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Because the written communication was personalized for the participant, inclusion of complex information was sometimes unavoidable. In our previous study, participants found the written summaries to be understandable (19). Participants were encouraged to discuss any aspect of the summary that they did not understand with the medical team.…”
Section: Interventionmentioning
confidence: 99%
“…In the outpatient setting, clinicians often provide written communication to the patient at the conclusion of the visit to improve comprehension and retention of medical information (17, 18). In a pilot study, we found that families of ICU patients who received daily written summaries reported improved understanding of the patient’s condition and improved communication with clinicians and other family members (19). The benefits of written updates were reported regardless of how frequently families visited in the ICU or interacted with the medical team.…”
mentioning
confidence: 99%
“…This process appears further augmented by cobinding of viral-ACE-2 complexes to either angiotensin-II type-1 receptors (AT1Rs) or vasopressin-V1 receptors (1). Additionally, multiple animal models consistently reported that proinflammatory AT1R signaling played a key mediating role in the development of experimental inflammatory lung injury (2). Further heightening interest in the RAS pertaining to COVID-19, there are already U.S. Food and Drug Administration-approved therapies that modulate the RAS including inhibitors of the ACE-1 enzyme (ACE-Is) as well as AT1R antagonists (AT1R blockade [ARB]) and agonists (synthetic angiotensin-II).…”
Section: Santa Barbara Camentioning
confidence: 99%
“…Both received the usual care, but the study group was also given the daily summaries. The summaries were created each afternoon by one investigator using a template they had previously piloted (2). The report summarized each of the patient’s problems, the etiology, whether there was improvement or decline, relevant diagnostic studies, and resultant therapies.…”
mentioning
confidence: 99%